2022
DOI: 10.1155/2022/7610297
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Nanosilica Effect on the Properties and Durability of Coir Reinforced Cement Brick

Abstract: The impact of nanosilica on the properties and microstructure of cement-based products has lately attracted a lot of attention. The effects of colloidal nanosilica (CNS) at different concentrations on the hydration process and performance of cement-based composites reinforced with coconut coir were examined in this study. CNS was applied at concentrations of 0%, 2%, 4%, and 6% by weight of cement, respectively. The samples were evaluated in terms of flexural test, scanning electron microscopy (SEM), thermograv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Many features of concrete like flow ability, mechanical properties, and durability can be enhanced by incorporating nanoparticles due to their excellent properties. Several researchers have undertaken various studies based on adding low-dose nanomaterials to replace the binder in concrete mixes in order to improve the characteristics of concrete, with successful outcomes [3][4][5][6]. The inclusion of nano-silica (NS), nano CaCO 3 , or nano TiO 2 particles demonstrated a great increase in the physical characteristics and durability of concrete due to its nucleation and micro-aggregate filling effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many features of concrete like flow ability, mechanical properties, and durability can be enhanced by incorporating nanoparticles due to their excellent properties. Several researchers have undertaken various studies based on adding low-dose nanomaterials to replace the binder in concrete mixes in order to improve the characteristics of concrete, with successful outcomes [3][4][5][6]. The inclusion of nano-silica (NS), nano CaCO 3 , or nano TiO 2 particles demonstrated a great increase in the physical characteristics and durability of concrete due to its nucleation and micro-aggregate filling effects.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a sustainable way to cut down on cement usage and increase the longevity of concrete, especially in coastal projects. [6] 2021 HishamShah.et.al., [7] 2022 concentrated on the various amounts of colloidal nanosilica (CNS) influenced the properties of cement composites reinforced with coconut coir. It was found that adding 4% CNS considerably improved the fibre/matrix bonding and pozzolanic methods, which in turn improved the flexural strength and microstructure of the samples.…”
Section: Introductionmentioning
confidence: 99%